2010
DOI: 10.1002/adfm.200901759
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Immobilization of Bioactives During 3D Powder Printing of Bioceramic Drug‐Release Matrices

Abstract: The combination of a degradable bioceramic scaffold and a drug‐delivery system in a single low temperature fabrication step is attractive for the reconstruction of bone defects. The production of calcium phosphate scaffolds by a multijet 3D printing system enables localized deposition of biologically active drugs and proteins with a spatial resolution of approximately 300 µm. In addition, homogeneous or localized polymer incorporation during printing with HPMC or chitosan hydrochloride allows the drug release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 32 publications
1
77
0
Order By: Relevance
“…3). Scaffolds 235 fabricated with similar composition and drying method to those 236 used in this work (Román et al, 2011) showed a porosity around 237 95%, with 30% for the pores with the highest diameter, around 65% (Vorndran et al, 2010). The release profiles of Figs.…”
mentioning
confidence: 78%
“…3). Scaffolds 235 fabricated with similar composition and drying method to those 236 used in this work (Román et al, 2011) showed a porosity around 237 95%, with 30% for the pores with the highest diameter, around 65% (Vorndran et al, 2010). The release profiles of Figs.…”
mentioning
confidence: 78%
“…Researchers have been attracted to the localized delivery of growth factors and drugs due to the potential for dose reduction, the reduced side effects compared to systemic delivery and the controlled and sustained release pattern [77]. Pore size, interconnectivity and geometry of scaffolds can also influence drug loading and control over release rate in vivo [78].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported systems that rely on the setting reaction of cements, an exothermic reaction that implies acidic media, both conditions in which the drug may be degraded [15,16].…”
Section: Introductionmentioning
confidence: 99%